The Impact of Educational Sessions on Anxiety Levels among Women Undergoing Caesarean Section: A Quasi-Experimental Study - Fatimah Alsufyani; Nouran Katooa; Ahlam Al-Zahrani; Ohood Felemban; Hanan Badr; Hala Thabet (MDPI AG, 2024)
Although the Caesarean section (CS) is considered a harmless surgery, it has various complications. Women scheduled for elective CSs often have high levels of anxiety due to a lack of knowledge. The aim of this quantitative quasi-experimental study was to determine the relationship between preoperative educational sessions and anxiety levels among women undergoing CSs. The study was conducted at the antenatal unit in the King Faisal Medical Complex (KFMC) in Taif, Saudi Arabia, using a structured interview questionnaire, the State-Trait Anxiety Inventory (STAI), and satisfaction interviews. A total of 50 pregnant women participated in this study, who were divided into two groups: 25 participants in the intervention group and 25 in the control group. Most participants (92%) in the intervention group had low anxiety levels following educational sessions, and 96% of the participants were very satisfied with the preoperative information they had been given. Women in the control group (again, 92%) had high anxiety levels, and there was a significant difference in the anxiety levels of the intervention and control groups (p ≤ 0.5) after the educational sessions. Providing proper preoperative education about CSs can reduce preoperative anxiety, improve patient outcomes, and enhance patients' involvement in their care and decision-making.